2017
DOI: 10.1371/journal.pone.0181633
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine acting at D1-like, D2-like and α1-adrenergic receptors differentially modulates theta and gamma oscillatory activity in primary motor cortex

Abstract: The loss of dopamine (DA) in Parkinson’s is accompanied by the emergence of exaggerated theta and beta frequency neuronal oscillatory activity in the primary motor cortex (M1) and basal ganglia. DA replacement therapy or deep brain stimulation reduces the power of these oscillations and this is coincident with an improvement in motor performance implying a causal relationship. Here we provide in vitro evidence for the differential modulation of theta and gamma activity in M1 by DA acting at receptors exhibitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 85 publications
5
10
0
Order By: Relevance
“…Increased principal neuron activity and glutamate may increase gamma through the activation of metabotropic glutamate receptors ( Whittington et al, 1995 ). Finally, dopamine D1Rs may be involved in gamma generation in M1 ( Özkan et al, 2017 ). Ketamine-initiated gamma may also involve D1Rs as we observed that ketamine-induced locomotion and gamma in M1 were eliminated when ketamine was delivered after delivery of a D1R antagonist ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased principal neuron activity and glutamate may increase gamma through the activation of metabotropic glutamate receptors ( Whittington et al, 1995 ). Finally, dopamine D1Rs may be involved in gamma generation in M1 ( Özkan et al, 2017 ). Ketamine-initiated gamma may also involve D1Rs as we observed that ketamine-induced locomotion and gamma in M1 were eliminated when ketamine was delivered after delivery of a D1R antagonist ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of DA transmission in M1 occurs by various neurodegenerative disorders such as PD, multiple sclerosis, and TBI ( Gaspar et al, 1991 ). According to pre-clinical and clinical findings of PD studies, the reduction of DAergic projections from VTA to M1 is accompanied by the appearance of exaggerated spectral power of theta, beta, and gamma frequency bands in M1( Nimmrich et al, 2015 ; Ozkan et al, 2017 ; Wang et al, 2015 ). In line with these studies, our findings showed that, the reduction of D 1 R and D 2 R levels in FLA and HLA is correlated with increased LFP power after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…The negative correlation of LFP power with the simultaneous decrease of D 1 R and D 2 R expressions may reflect the synergistic effects of both receptors on the modulation of M1 neural activity ( Awenowicz & Porter, 2002 ). These effects may be mediated directly via the expression of D 2 R in glutamatergic pyramidal neurons or indirectly through an expression of D 1 Rs on GABAergic interneurons ( Ozkan et al, 2017 ; Vitrac et al, 2014 ). It is noteworthy that the current study was designed to assess the effect of SCI on oscillatory activity and the DAergic system of M1, rather than to determine the underlying mechanism of their interactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations